Altitude-adaption of gut microbiota in Tibetan chicken - Xiaxia Du; Fugui Li; Fanli Kong; Zhifu Cui; Diyan Li; Yan Wang; Qing Zhu; Gang Shu; Yaofu Tian; Yao Zhang; Xiaoling Zhao (Poultry Science, 2022)
ABSTRACT: Low oxygen levels and extremely cold weather in high-altitude environments requires more energy intake to maintain body temperature in animals. However, little is known about the characteristics of cecal and ileac microbiota in Tibetan chicken and how the high and low altitude environments affect the gut microbiota communities in Tibetan chicken. In the present study, In the present study, Tibetan chickens (Group HA, 3572 m, 578.5 Pa) and their introduced flatland counterparts (Group LA, 580 m, 894.6 Pa) in the cecum and ileum to identify the possible bacterial species that are helpful for their host in environmental adaption. High-throughput sequencing was used to sequence the V3 to V4 hypervariable regions of the bacterial 16S rRNA gene. By comparing the gut microbial diversity of HA chicken with that of LA, the results indicated that the microbial diversity of the cecum and ileum in group HA was significantly lower (P < 0.05) than those in group LA. The cecum microbiome maintained higher population diversity and richness than the ileum (P < 0.05). Four phyla Firmicutes, Bacterioidetes, Actinobacteria, and Proteobacteria were dominant in two groups. Interestingly, there were significant differences in abundance ratio among the four groups (P < 0.05). The predominant bacteria in HA and LA ileum belong to Proteobacteria and Firmicutes, whereas in cecum, Bacterioidetes and Actinobacteria were predominant in both groups (P < 0.05). Correlation analysis showed that Sporosarcina, Enterococcus, and Lactococcus were strongly related to air pressure, and Peptoclostridium and Ruminococcaceae_UCG-014 are related to altitude and gut microbiota of LA group was influenced by altitude, while HA group affected by air pressure. Meanwhile, the Ruminococcus-torques-group was negatively correlated with the relative abundance of Paenibacillus, and positive correlated with those of other microorganisms. Furthermore, HA has higher abundance of microbiota involved in energy and glycan biosynthesis metabolism pathway, while LA has higher abundance of microbiota involved in membrane transport, signal transduction, and xenobiotics biodegradation and metabolism. Generally, our results suggested that the composition and diversity of gut microbes changed after Tibetan chickens were introduced to the plain. Tibetan chicken may adapt to new environment via reshaping the gut microbiota. Gut microbes may contribute to the host adaption to high altitude environments by increasing host energy and glycan biosynthesis.